Array Design Of Smart Antenna - Lau, Hock Yan (Universiti Sains Malaysia, 2006)
Smart antennas have recently received increasing interest for improving of wireless system. The so-called 4x4 Butler matrix is a passive circuit which gives us the ability to get a main beam from an antenna array into the one of the four beam directions. The matrix is designed at 2GHz and implemented on a microstrip structure using conventional manufacturing process. The matrix consists of hybrid couplers, crossover, phase shifters and patch antennas. The main purpose of this project is to reduce the number of couplers and antennas in the matrix from the original design. The matrix is designed and simulated by using Advanced Design System (ADS) and implemented on FR4 PCB. The measurements that will concern in this project are return losses, phase shifts, antennas gain and radiation pattern. The new design’s results will be comparing with the original and may prove the new design is operate in the same way.